Reduced steady-state levels of rbcS mRNA in plants kept in the dark are due to differential degradation. - Fritz, C C (1991)
When plants are placed in the dark, the level of the abundant mRNA encoding the small subunit of ribulose-1,5-bisphosphate carboxylase (rbcS) declines rapidly. We present evidence demonstrating an active degradation of rbcS mRNA in the dark. Detailed analysis shows that transcripts originating from different members of the rbcS gene family are differentially affected by this degradation. This phenomenon is not common to all light-regulated plant genes since the mRNA for ST-LS1, another leaf-specific and light-induced gene, is not degraded in the dark within the same time scale.